"Being The Type of Lover...": Gender Differentiated Reasons for Non-Use of Condoms by Sexually Active Heterosexual Students - Wood, Catherine; Foster, Don (PINS-Psychology in Society, 2026)
This qualitative study explores reasons for heterosexual students not using condoms as a means of protection against HIV transmission. Twenty sexually active, heterosexual University of Cape Town (UCT) students (10 women and 10 men), all of whom had relatively good knowledge about HIV transmission, participated in individual, semi-structured interviews. Data were first analyzed by method of ethnographic content analysis, but limitations of this approach lead to the predominant use of a discursive analysis. Seven themes are highlighted: negative attitudes towards condoms; condoms seen primarily as contraceptives; perceived invulnerability; stage of relationship and condom use; gender-role expectations; gendered power relations; and a new women-centred discourse of sexuality. Findings provide insight into gender differences in safer sex negotiation: the most significant being that women’s real or perceived sense of powerlessness within sexual encounters prevents them from insisting on the use of condoms. Implications of these findings for future prevention programmes are discussed.